Survival Following Segmentectomy or Lobectomy in Patients With Stage IB Non-small-cell Lung Cancer - Hao, Bo; Zhang, Lin; Fan, Tao; Liu, Bohao; Jiang, Wenyang; Hu, Hao; Geng, Qing (Frontiers in Oncology, 2020)
Abstract Background: Lobectomy with mediastinal lymph node dissection has always been recognized as the standardized treatment for early stage non-small cell lung cancer. However, the feasibility of segmentectomy performed in non-small lung cancer patients with stage ⅠB remains controversial. The present study aims to investigate whether the outcome of patients with stage ⅠB underwent segmentectomy was comparable to those who underwent lobectomy. Method: We retrospectively collected data of 11010 patients with primary stage ⅠB non-small cell lung cancer from the Surveillance, Epidemiology, and End Results database. Overall survival and lung cancer specific survival were assessed among patients who were performed lobectomy or segmentectomy. To further investigate the impact of surgical procedure on patients with different tumor size, subgroups stratified by tumor size were performed. Results: A total of 11010 patients who were pathologically confirmed stage ⅠB were included, of whom 10453 patients received lobectomy and 557 received segmentectomy. Both univariate and multivariate cox regression analyses of overall survival showed that the survival of the patients who have undergone lobectomy was longer than that of segmentectomy. However, multivariate analysis for lung cancer specific survival showed that there was no significant difference between patients who underwent lobectomy and who underwent segmentectomy. And subgroup analyses illustrated that, when tumor size≤ 40 mm and > 30 mm, lobectomy was associated with better overall survival; while tumor size ≤ 30 mm, the outcome showed no significant difference. As for lung cancer specific survival, no significant difference was observed regardless of tumor size. Conclusion: Segmentectomy achieved an equivalent OS and LCSS for stage ⅠB NSCLC patients with stage ⅠB compared with lobectomy when tumor size ≤30 mm; When tumor T > 30 mm and T≤40 mm, lobectomy yielded a longer survival. Segmentectomy is likely to be performed in elder patients with smaller tumor size, and we recommend that segmentectomy maybe acceptable for the selected stage ⅠB patients who tumor size ≤30 mm and age >69.